Efficient Solid-Phase-Based Total Synthesis of the Bisintercalator TANDEM - Malkinson, John P; Anim, Michael K; Zloh, Mire; Searcey, Mark; Hampshire, Andrew J; Fox, Keith R (Journal of organic chemistry, 2005)
In this article, the first solid-phase-based total synthesis of TANDEM, a synthetic analogue of triostin A, is described. In initial studies, the synthesis incorporated depsipeptide formation, introduction of chromophores, and disulfide bond formation on the solid phase, prior to a final solution-phase macrolactamization, to give the target molecule. Although pure TANDEM was obtained in an overall yield comparable to those for all syntheses to date, the yield of the final cyclization was low (11%). A more efficient approach involved removal from the solid phase prior to disulfide bond formation. The resulting linear peptide underwent macrolactamization under mild conditions and high dilution. Final disulfide bond formation was essentially quantitative and gave the target molecule, TANDEM, in an overall yield of 18%. The final compound was assessed for its ability to bind to 5‘-TpA sequences on DNA by DNase I footprinting. This efficient synthesis sets the stage for a study of the structure−activity relationship of TANDEM and the natural product triostin A, with analogues containing “point mutations” at every site within the cyclic compounds.